(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This discussion explores the UN Security Council’s role in shaping international law and influencing State behavior. It examines how the Council reaches findings and opinions on legal matters and the impact of these decisions on global state conduct, highlighting its pivotal role in the global legal order.